2019
DOI: 10.3389/fonc.2019.00896
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circulating Lymphocyte Populations and Outcome After Stereotactic Body Radiation Therapy in Patients With Hepatocellular Carcinoma

Abstract: Background and Objective: Radiation-induced lymphopenia has a tangible impact on overall survival (OS) in multiple solid tumors. We investigated the association between circulating lymphocyte populations (CLPs) before and after stereotactic body radiation therapy (SBRT) and OS in patients with hepatocellular carcinoma (HCC).Materials and Methods: Seventy-eight HCC patients treated with SBRT between January 2013 and June 2017 were retrospectively analyzed. Baseline and post-treatment total peripheral lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Emerging evidence showing radiation-induced lymphopenia (RIL) or PLC-related parameters are associated with poor survival outcomes in several solid tumors (9)(10)(11)(12)(13)(14). Cho et al reported RIL was a potential predictor for ipsilateral breast tumor recurrence in 216 patients with early breast cancer treated with breast-conserving therapy (BCT) (15).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence showing radiation-induced lymphopenia (RIL) or PLC-related parameters are associated with poor survival outcomes in several solid tumors (9)(10)(11)(12)(13)(14). Cho et al reported RIL was a potential predictor for ipsilateral breast tumor recurrence in 216 patients with early breast cancer treated with breast-conserving therapy (BCT) (15).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the impact of the follow-up period on circulating lymphocyte subsets following liver transplantation is unclear. Zhuang et al detected that the cell counts of T, TCD4, TCD8, B, and NK dropped profoundly shortly after stereotactic body radiation therapy and gradually recovered 2 months later ( 37 ). Similarly, we observed that the absolute numbers of lymphocyte subsets were reduced in LTR with short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RT kills not only TILs but also peripheral blood lymphocytes passing through the irradiation field and may induce lymphopenia. Of note, there are emerging data revealing that severe lymphopenia is associated with a poor prognosis in patients with different tumors (53)(54)(55). Therefore, the size of the radiation field should be reasonably limited when investigating combination therapy (7).…”
Section: Discussionmentioning
confidence: 99%